Graphene, carbon nanotubes, and nanostuctures : techniques and applications - Morris, James E.; Iniewski, Krzysztof (Devices, circuits, and systems, 2013)
"Assembling the latest research in the field of nanofabrication technology in one place, this book exposes readers to myriad applications that nanofabrication technology has enabled. With contributions from both academia and industry, this book can be used as a reference, advanced graduate course, or for investers trying to familiarize themselves with the nanofabrication landscape"--